Characterization of Structural and Physicochemical Properties of an Exopolysaccharide Produced by Enterococcus sp. F2 From Fermented Soya Beans - Jiang, Guangyang; Gan, Longzhan; Li, Xiaoguang; He, Juan; Zhang, Shihao; Chen, Jia; Zhang, Ruoshi; Xu, Zhe; Tian, Yongqiang (Frontiers in Microbiology, 2021)
This work aims to evaluate the structure and properties of a novel exopolysaccharide (EPS-F2) produced by Enterococcus sp. F2 isolated from fermented soya beans. Results illustrated that EPS-F2 was neutral homo-exopolysaccharide containing solely glucose, with a molecular weight of 1.108×108 g/mol. Structural analyses revealed that the EPS-F2 contained →6)-α-D-Glcp-(1→ linkages in the main chain and →3, 6)-α-D-Glcp-(1→ branch chain. It was shown that EPS-F2 was an amorphous-crystalline polymer and had a branched molecule surface structure. Moreover, EPS-F2 possessed excellent thermal stability with a degradation temperature of 266.6 °C and a melting point of 122.6 °C. The water holding capacity (WHC), water solubility index (WSI) and oil holding capacity (OHC) of EPS-F2 were 882.5 ± 20.44%, 14.62 ± 0.33% and 1867.76 ± 11.33%, respectively. EPS-F2 also exhibited good emulsifying activity against various edible oils. Steady shear experiments further reflected that EPS-F2 exhibited pseudoplasticity, under various conditions. Dynamic oscillatory measurements indicated that EPS-F2 had liquid-like behavior at a low concentration (2.5%), while had solid-like behavior at high concentrations (3.0 and 3.5%). Together, EPS-F2 may be a good candidate that can be applied in various industries.